On diffraction Fresnel transforms for Boehmians - Al-Omari, Shrideh Khalaf Qasem; Kilicman, Adem (Hindawi Publishing Corporation, 2011)
The theory of the diffraction Fresnel transform is extended to certain spaces of Schwartz distributions. In the context of Boehmian spaces, the diffraction Fresnel transform is obtained as a continuous function. Convergence with respect to δ and Δ is also defined.